Case Study of Intergroup Conflict in Student Groups at Senior High School State 1 Kakas Minahasa Regency - Sumolang, Nortje (JR Education, 2025)
This research was conducted at SMA Negeri 1 Kakas, and is described as follows: (1) types of conflict between student groups, (2) school strategies for handling conflict. This study employed qualitative research. The data collection techniques used were (1) observation, (2) interviews, (3) documentation studies, (4) and a combination of the three (triangulation). The research instruments were self-research, field notes, and an interview guide. The data obtained were then analyzed using the following steps: (a) Credibility, (b) Tranferability, (c) Dependability. Based on the research results, the following findings were obtained: 1. From the research results obtained by the researcher through interviews with 26 groups of students, the conflicts that occurred between student groups at SMA Negeri 1 Kakas were caused by: (1) Conflicts between student groups arose due to mutual teasing, (2) Conflicts between student groups occurred due to misunderstandings, (3) Conflicts between student groups were caused by jealousy. 2. Based on the findings from the 26 groups, the researcher interviewed teachers at SMA Negeri 1 Kakas, and most of the teachers supported the statements from the student groups. The researcher also interviewed the principal of SMA Negeri 1 Kakas, and he supported the statements from the teachers. Next, the researcher interviewed security at SMA Negeri 1 Kakas, and he supported the statements from the students, teachers, and the principal.